2015
DOI: 10.1016/j.aquabot.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Clonal integration in Ludwigia hexapetala under different light regimes

Abstract: a b s t r a c tPhysiological integration among ramets of invasive plant species may support their colonization and spread in novel aquatic environments where growth-limiting resources are spatially heterogeneous. Under contrasting light conditions, we investigated how clonal integration influences growth, biomass allocation and morphology of Ludwigia hexapetala, an emergent floating-leaved macrophyte that is highly invasive in a range of wetland habitat types. In aquatic mesocosms, stolons of offspring ramets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…; Glover et al . ), a recent meta‐analysis showed that it generally has no significant costs (Song et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Glover et al . ), a recent meta‐analysis showed that it generally has no significant costs (Song et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…; Glover et al . ), we can speculate that established ramets of amphibious clonal plants in terrestrial habitats can support young ramets to initially establish in aquatic habitats ( e.g . wetlands) heavily contaminated with Cd.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, environmental conditions are usually spatially heterogeneous (Glover et al ; Wang et al ). One potential benefit of clonality is that ramets, connected by belowground rhizomes or aboveground stolons, can share resources and signals, thereby increasing the growth and competition of clonal plants in numerous environments with heterogeneous distribution of light, water, nutrients and competitors (Stuefer et al ; Yu et al ; Song et al ; You et al ; Roiloa et al ; Wang et al ).…”
Section: Introductionmentioning
confidence: 99%
“…One strategy by which clonal plants cope with environmental heterogeneity is physiological integration, i.e., the capacity to share resources among interconnected ramets (Hutchings and Wijesinghe, 1997 ; Herben and Suzuki, 2001 ; Song et al, 2013 ; Roiloa et al, 2014 ; Dong et al, 2015 ). Physiological integration enables parent ramets to support offspring ramets (Matlaga and Sternberg, 2009 ; Oborny and Hubai, 2014 ; Roiloa et al, 2014 ; Glover et al, 2015 ) and ramets growing in favorable conditions to support those in unfavorable conditions (Roiloa et al, 2007 ; Xu L. et al, 2012 ; Kui et al, 2013 ; Tuya et al, 2013 ; Cornelissen et al, 2014 ; Luo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%